Development of Walking in Place System based on Zero Crossing Algorithm - Yang, Hongbiao; Sawhney, Rapinder; Ji, Shuguang; Wade, Eric R. (International Journal of Virtual Reality, 2016)
Walking in Place (WIP) is a way to facilitate locomotion tasks in the virtual environment while keeping the subject relatively static in the physical environment. This technique enables subjects to walk in a virtual space with limited physical space requirements. This paper introduces a burden-free and error-tolerant system to track the subjects’ walking and turning motions, and to translate these motions to the virtual environment using the Microsoft Kinect. In addition, we introduce a zero crossing based algorithm that analyzes joint position data, detects the knee coordinates exchange pattern, and produces locomotion with low latency and jerkiness.